THE ROLT MEMORIAL LECTURE 2013: THE PUBLIC BENEFIT OF INDUSTRIAL HERITAGE — TAKING A POSITIVE VIEW. (November 2014) - Oglethorpe, Miles
Abstract : This paper contains a summary of the 2013 Rolt Memorial Lecture, delivered to the annual conference of the Association for Industrial Archaeology in Dundee on 11 August 2013. The lecture commenced by observing the extent to which Industrial Heritage has progressed in recent decades, noting that it is now embedded in many national institutions in the UK, and has been 'mainstreamed' into heritage more generally. However, it now faces several serious challenges, not least the diminishing number and increasing age of activists, together with cuts to the State sector. It is argued, nevertheless, that industrial heritage has more to offer now than ever before and that more effective political engagement is required to ensure that this is understood by those with power and influence over the historic environment. To illustrate this point, current work on the Industrial Heritage Strategy for Scotland is discussed, together with the potential impact of the UK's latest industrial World Heritage nomination, the Forth Bridge.